Effects of sex, race, and ethnicity on primary and subspecialty healthcare use by autistic children in Florida: A longitudinal retrospective cohort study (2012–2018). (June 2022) - Angell, Amber M.; Varma, Deepthi S.; Deavenport-Saman, Alexis; Yin, Larry; Solomon, Olga; Bai, Chen; Zou, Baiming
Abstract: Background: Autistic children and youth have high rates of co-occurring conditions, but little is known about how autism subgroups (girls, non-White children) access healthcare to treat them. The purpose of this longitudinal retrospective cohort study was to investigate differences by sex, race, and ethnicity in non-acute (primary and subspecialty) healthcare use by autistic children and youth. Method: We used the OneFlorida Data Trust to measure healthcare use for 82, 566 autistic children ages 1–21 (2012–2018). We investigated (1) the odds of using any healthcare and (2) annual healthcare usage rates. We adopted a logistic regression and multiple linear regression for each of the dependent variables (total non-acute, primary care, gastroenterology (GI), developmental-behavioral pediatrics (DBP), psychiatry/psychology, neurology, and total subspecialty visits), adjusting for potential confounders (sex, race, ethnicity, age at visit, insurance type, urbanicity, and co-occurring conditions). Results: Autistic boys had significantly higher odds of any neurology and psychiatry/psychology visits, but lower annual rates of primary care, GI, and neurology visits. Black/African American autistic children had significantly higher odds of any primary care, DBP, and neurology visits, but lower odds of any GI visits, and lower annual rates of primary care, GI, DBP, and neurology visits. Hispanic/Latinx autistic children had significantly higher odds of any primary care, DBP, and neurology visits, but lower odds of psychiatry/psychology visits; and higher annual rates of neurology visits, but lower annual rates of GI, DBP, and psychiatry/psychology visits. Conclusions: We found significant differences by sex, race, and ethnicity in non-acute healthcare use by autistic children. Highlights: Autistic boys had higher odds ofneurology and psychiatry/psychology visits, but fewer to primary care, GI, and neurology visits, than girls. Black autistic children had higher odds of primary care, DBP, and neurology visits, but lower odds of GI visits, than White children. Black autistic children had fewer primary care, GI, DBP, and neurology visits than White children. Latinx autistic children had higher odds of primary care, DBP, and neurology visits, but lower odds of psychiatry/psychology visits, than non-Latinx children. Latinx autistic children had more neurology visits, but fewer GI, DBP, and psychiatry/psychology visits, than non-Latinx children.